Immunology aspects of playing. - Pacheco Romero, José (2015)
The obstetrics gynecology has been linked to the first knowledge of immunology. At the origin of immunology, in 1899 and 1900. Landsteiner, Metchniloff and Metalnikoff regardless showed that injecting sperm or testicular extracts to laboratory animals resulted in the formation of detectable antibodies in the serum and the immobilized sperm. Later, the first successful blood transfusion is a variety of transplant, was administered by an obstetrician to a patient with bleeding. And the first attempt to transplant a kidney was pregnant with intrauterine infection, shock and anuria. Recently, we are aware various phenomena existing immunological infertility, oncology, fetal erythroblastosis by Rh incompatibility, among others, and there is great interest in knowing what kind of maternal-fetal graft occurs during pregnancy allows the fetus not be rejected during 40 weeks of the pregnancy.